As licenciaturas interdisciplinares no cenário nacional: implantação e processo - Luz, Aline Souza da (2018)
The aim of this study is to understand the Interdisciplinary Licenciates (IL) all over Brazil, elucidating the context which these courses emerged and were implemented, their bases and formative processes. The ILs are teacher training courses, in college, composed by fields of knowledge; their premise is the interdisciplinarity. Methodologically we adopted the following steps: after the national mapping of ILs, we selected a course in each region of Brazil: Integrated Licenciate in Science Education, Mathematics and Languages (UFPA); Interdisciplinary Licenciate in Languages and Codes/Music (UFMA); Natural Science Licenciate (UNB); Science Degree – Licenciate (UNIFESP) and Human Science Degree – Licenciate (UNIPAMPA). For the data collection we used: documental analysis of Course Projects and laws related to IL and teacher training, semi-structured interviews with the coordinators and/or NDE membership, adding up to 12 teachers and, on line closed survey, in the total of 51 people answering. The study identified that the Interdisciplinary Licenciates implementation is the result of a set of factors, pointing out the policy expansion of college education introduced by REUNI and, the recurring speech (and produced) of quality lack, related to the existing teachers training and the lack of teachers in some basic education areas. The setting of main part in Interdisciplinary Licenciates courses occured with institutional confrontations, through power relations. This way, we did not identify a more systematic or politically organized process to the IL setting up, which generates ambiguities and, maybe incoherence about the title and ―qualification‖ for the student who is being graduated. It was not found a study or planning that justify the meeting for the field of knowledge. It was confirmed that each course is very peculiar about its own understanding related to interdisciplinar education, as well as its curricular organization. It was noticed that this diversity is, partly, because of the standardization abscence in these courses. Some elements which become difficult the consolidation and development of these courses were: ●The University‘s organization and culture are mostly disciplinary. ● The courses have a limited pedagogical and management structure to the interdisciplinary proposals; limited fomentation to the teachers continuous training and too many activities which might undermine the effectiveness of a collective planning ● the teaching staff: the lack of qualification and investiment for continuous training ● the students seemed to be insecure and resistant towards the proposals because of the possible dificulty of getting a job ● the labour market and the society to understand what is the course in fact and the graduated Interdisciplinary Licenciate student‘s attributions. Because of these dificulties, the interdisciplinarity announced by the Interdisciplinary Licenciates, limitations and problems to be effectively implemented into the courses. We consider that, the Interdisciplinary Licenciates offer some progress, but also a lot of limitations which need to be reviewed and faced, moreover conceptually and legally. Therefore, we state the theory that the Interdisciplinary courses, which were analysed, have the capacity to accomplish a paradigmatic shift related to the teachers‘ qualifications, but not with the current concepts which showed their implementatios and developments, once we consider that these courses still did not really break up with the perspective of an education focused on Technical Rationality.